Halogen-free flame-retardant prepreg layer and polypropylene composite material comprising same
By using a combination technology of a halogen-free flame-retardant prepreg layer and ablation-resistant polypropylene composition layer in thin-walled polypropylene composite materials, the shortcomings of existing materials in terms of ablation and ball impact resistance are solved, and a high-performance polypropylene composite material is achieved.
Patent Information
- Application Number
- CN202510366318.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-06-17
- Estimated Expiration
- 2045-03-26
AI Technical Summary
The existing thin-walled polypropylene composite materials have shortcomings in ablation resistance and ball impact performance, and cannot meet the high requirements for applications such as battery covers in new energy vehicles.
A halogen-free flame-retardant prepreg layer, including glass fiber cloth and a prepreg with high content of flame retardant, is prepared by impregnation, rolling, baking and other processes, and combined with ablation-resistant polypropylene composition layer, a polypropylene composite material is formed.
It significantly improves the ablation resistance and ball impact performance of polypropylene composite materials, and has good self-supporting properties. It can maintain stability at high temperatures, with a burn-through time of 600s, the back temperature does not exceed 180℃, and the ball impact height does not be less than 2m.
Smart Images

Figure BDA0005330111830000011 
Figure BDA0005330111830000031 
Figure BDA0005330111830000071
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thermoplastic plastics, and more specifically, relates to a halogen-free flame-retardant prepreg layer and a polypropylene composite material comprising the same. Background Art
[0002] The new energy industry is booming, the installed capacity of power batteries and energy storage batteries has increased sharply, and the market driving force is strong. Among them, as the core component for energy storage and conversion, the safety of the battery pack is directly related to the stable operation of the entire system and user safety. According to the domestic standard GB / T31467.3-2015, the battery pack must pass strict fire resistance tests and strictly control the emission of toxic and harmful gases during the combustion process.
[0003] In the prior art, piperazine salts and melamine salts are used in combination to achieve the ablation resistance of thin-walled polypropylene composite materials. With the trend of thinning of large parts such as the battery upper cover of new energy vehicles, it cannot meet the requirements of high ablation resistance, reduction of the back surface temperature, and improvement of the material's ball drop impact resistance. Therefore, there is a need in the art to develop a thin-walled polypropylene composite material with good ablation resistance and good ball drop impact performance. Summary of the Invention
[0004] The purpose of the present invention is to overcome the defects or deficiencies in the poor ablation resistance and ball drop impact performance of thin-walled polypropylene composite materials in the prior art, and to provide a halogen-free flame-retardant prepreg layer and a polypropylene composite material comprising the same.
[0005] Another purpose of the present invention is to provide a preparation method of the halogen-free flame-retardant prepreg layer.
[0006] Another purpose of the present invention is to provide a preparation method of the polypropylene composite material.
[0007] Another purpose of the present invention is to provide an application of the polypropylene composite material.
[0008] To achieve the above purposes, the present invention is realized through the following technical solutions:
[0009] A halogen-free flame-retardant prepreg layer, comprising a glass fiber cloth and a prepreg. The thickness of the glass fiber cloth in the prepreg layer is 0.2 - 0.4 mm, and the grammage is 150 - 450 g / m 2 , and the thickness of the halogen-free flame-retardant prepreg layer is 0.3 - 0.8 mm.
[0010] Furthermore, the prepreg comprises the following components calculated by weight:
[0011]
[0012] Furthermore, the flame retardant content in the prepreg is not less than 28 wt%, such as but not limited to not less than 28 wt%, 29 wt%, 30 wt%, 31 wt%, 32 wt%, 33 wt%, 34 wt%, 35 wt%, 37 wt%, 40 wt%, 42 wt%, 45 wt%, 48 wt%, 50 wt%, 52 wt%, 55 wt%, 58 wt% or 60 wt%, etc., as well as the specific point values between the above point values. Due to space limitations and for the sake of simplicity, the specific point values included in the scope of the present invention are not exhaustively listed herein.
[0013] Furthermore, the flame retardant content in the prepreg is 33 wt% - 55 wt%.
[0014] Furthermore, the flame retardant includes piperazine salt and melamine salt.
[0015] It should be noted that the thickness of the halogen-free flame retardant prepreg layer of the present invention can be adjusted by adjusting the thickness of the fiberglass cloth and the impregnation amount of the prepreg.
[0016] Furthermore, the thickness of the halogen-free flame retardant prepreg layer in the present invention is 0.3 - 0.8 mm, such as but not limited to 0.3 mm, 0.35 mm, 0.4 mm, 0.45 mm, 0.5 mm, 0.55 mm, 0.6 mm, 0.65 mm, 0.7 mm, 0.75 mm or 0.8 mm, etc., as well as the specific point values between the above point values. Due to space limitations and for the sake of simplicity, the specific point values included in the scope of the present invention are not exhaustively listed herein.
[0017] Furthermore, the number average molecular weight of the compatibilizer A is 5000 - 10000, such as but not limited to 5000, 5500, 6000, 6500, 7000, 7500, 8000, 8500, 9000, 9500 or 10000, etc. The number average molecular weight of the compatibilizer A can be measured by gel permeation chromatography (GPC) method based on polystyrene standard.
[0018] Furthermore, the melting point of the compatibilizer A is 130 - 140 °C, such as but not limited to 130, 131, 132, 133, 134, 135, 136, 137, 138, 139 or 140 °C, etc.
[0019] Furthermore, the compatibilizer A is maleic anhydride grafted polypropylene.
[0020] Further, the melt flow rate of the polypropylene resin A measured according to the standard of GB / T 3682.1-2018 at 230°C under a load of 2.16 kg is 60 to 150 g / 10 min. Specifically, it can be 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145 or 150 g / 10 min, etc.
[0021] Furthermore, the melt flow rate of the polypropylene resin A measured according to the standard of GB / T 3682.1-2018 at 230°C under a load of 2.16 kg is 80 to 120 g / 10 min.
[0022] Further, the halogen-free flame retardant prepreg layer further comprises 0.3 to 1 part of an auxiliary agent.
[0023] Further, the auxiliary agent includes one or more of an antioxidant, a lubricant, a weathering agent or a color powder.
[0024] The present invention also provides a method for preparing the above-mentioned halogen-free flame retardant prepreg layer, which comprises the following steps:
[0025] Mix the components other than the glass fiber cloth in the halogen-free flame retardant prepreg layer to obtain a prepreg, impregnate the glass fiber cloth with the prepreg, roll press, bake, film coat and wind up to obtain the halogen-free flame retardant prepreg layer.
[0026] Specifically, the impregnation of the glass fiber cloth with the prepreg is to apply the prepreg on the surface of the glass fiber cloth at a temperature of 220 to 230°C, achieve double-sided impregnation through a sizing process, use an infrared sensor to monitor the distribution of the sizing liquid in real time, and dynamically adjust the spraying amount and the conveying speed to ensure the uniformity of the impregnation process.
[0027] The present invention also provides a polypropylene composite material, which comprises an ablation-resistant polypropylene composition and the above-mentioned halogen-free flame retardant prepreg layer; the thickness of the polypropylene composite material ≤ 1.8 mm.
[0028] It should be noted that the thickness of the polypropylene composite material ≤ 1.8 mm, such as but not limited to ≤ 1.8 mm, 1.7 mm, 1.6 mm, 1.5 mm, 1.4 mm, 1.3 mm, 1.2 mm, 1.1 mm or 1 mm, etc., as well as the specific point values between the above point values. Due to space limitations and for the sake of simplicity, the specific point values included in the above range are not exhaustively listed in the present invention.
[0029] Further, the thickness of the polypropylene composite material ≤ 1.5 mm.
[0030] In some preferred embodiments, the ablative-resistant polypropylene composition layer comprises the following components calculated by weight:
[0031]
[0032] Furthermore, the melt flow rate of the polypropylene resin B measured according to the standard of GB / T 3682.1-2018 at 230 °C under a load of 2.16 kg is 20-50 g / 10 min. Specifically, it can be 20, 22, 25, 28, 30, 32, 35, 38, 40, 42, 45, 48 or 50 g / 10 min, etc.
[0033] Even further, the melt flow rate of the polypropylene resin B measured according to the standard of GB / T 3682.1-2018 at 230 °C under a load of 2.16 kg is 25-40 g / 10 min.
[0034] Furthermore, the glass fiber is chopped glass fiber. By using the ablative-resistant polypropylene composition layer and the halogen-free flame-retardant prepreg layer in the present invention, good ablative resistance and falling ball impact performance can be achieved with chopped glass fiber.
[0035] Specifically, the average diameter of the chopped glass fiber is 10-15 μm, and the average length is 3-6 mm.
[0036] Furthermore, the compatibilizer B comprises maleic anhydride-grafted polyolefin.
[0037] Furthermore, the compatibilizer B is maleic anhydride-grafted ethylene-octene copolymer.
[0038] Furthermore, the piperazine salt comprises one or more of piperazine phosphate, piperazine pyrophosphate or piperazine polyphosphate.
[0039] Furthermore, the melamine salt comprises one or more of melamine phosphate, melamine pyrophosphate or melamine polyphosphate.
[0040] The content of the flame retardant in the ablative-resistant polypropylene composition layer is not less than 20 wt%, for example, but not limited to, not less than 20 wt%, 21 wt%, 22 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, 28 wt%, 29 wt%, 30 wt%, 31 wt%, 32 wt%, 33 wt%, 34 wt%, 35 wt%, 36 wt%, 37 wt%, 38 wt%, 39 wt% or 40 wt%, etc., as well as the specific point values between the above point values. Due to space limitations and for the sake of simplicity, the specific point values included in the above range are not exhaustively listed in the present invention.
[0041] Furthermore, the flame retardant comprises piperazine salt and melamine salt.
[0042] Further, the synergistic flame retardants in the prepreg and the ablative-resistant polypropylene composition layer include one or more of zinc oxide, magnesium oxide, aluminum oxide, lanthanum oxide, or silicon dioxide.
[0043] Further, the ablative-resistant polypropylene composition layer further includes 1 to 3 parts of a fluxing agent.
[0044] Further, the fluxing agent includes one or more of ammonium borate, zinc borate, boron frit, low-melting-point glass powder, nano-sepiolite, or montmorillonite.
[0045] Specifically, the D50 particle size of the fluxing agent is 6 to 10 μm.
[0046] Further, the ablative-resistant polypropylene composition layer further includes 0.3 to 1 part of an auxiliary agent.
[0047] Further, the auxiliary agent includes one or more of an antioxidant, a lubricant, a weathering agent, or a color powder.
[0048] In the present invention, the antioxidant can be a commonly used antioxidant, such as but not limited to including hindered phenol antioxidants and / or phosphite antioxidants.
[0049] The hindered phenol antioxidants include one or more of pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (Irganox 1010), tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanurate (antioxidant 3114), ethylene bis(oxyethylene) bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate] (Irganox 245), 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)acrylic acid]-1,1-dimethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane (ADK AO-80), N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxybenzamide) (Irganox 1098), 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (Irganox 259), or n-octadecyl β-(4-hydroxy-3,5-di-tert-butylphenyl)propionate (Irganox 1076).
[0050] The phosphite antioxidants are one or more of tris(2,4-di-tert-butylphenyl) phosphite (Irganox 168), bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite (PEP-36), or 627A.
[0051] In the present invention, common lubricants can be selected, such as but not limited to one or several of vinyl bisstearamide, polysiloxane, calcium stearate, magnesium stearate, zinc stearate, PE wax, or PP wax.
[0052] In the present invention, common weathering agents can be selected, such as but not limited to hindered amine light stabilizers and benzotriazole ultraviolet light absorbers.
[0053] Specifically, the hindered amine light stabilizer is at least one of bis(2,2,6,6-tetramethylpiperidyl) sebacate, polymer of N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl)-1,6-hexanediamine and 2,4,6-trichloro-1,3,5-triazine.
[0054] Specifically, the benzotriazole ultraviolet light absorber is one or more of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole (UV-P), 2-(2'-hydroxy-3',5'-bis(α,α-dimethylbenzyl)phenyl)benzotriazole (UV-234), 2-(2'-hydroxy-3-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole (UV-236).
[0055] The present invention also provides a preparation method of the above polypropylene composite material, comprising the following steps:
[0056] S1. Mix the components in the ablative-resistant polypropylene composition layer evenly, and obtain injection molding pellets through melt blending and extrusion granulation.
[0057] S2. Cut the halogen-free flame retardant prepreg layer described in step S1 to the target product size, heat it and put it into an injection molding die, and inject the injection molding pellets described in step S1 into the injection molding die after melting through an injection molding machine, and obtain the polypropylene composite material after pressure holding and cooling.
[0058] Specifically, the extrusion granulation in step S1 is carried out in a twin-screw extruder.
[0059] Specifically, the feeding speed of the twin-screw extruder is 250 - 350 rpm.
[0060] Specifically, the temperature of the first zone of the twin-screw extruder is 150 - 160 °C, the temperature of the second zone is 180 - 190 °C, the temperature of the third to fifth zones is 210 - 230 °C, and the temperature of the die is 200 - 210 °C.
[0061] Specifically, the main machine speed of the twin-screw extruder is 300 - 500 rpm.
[0062] Specifically, the heating time in step S2 is 10 - 20 min.
[0063] Specifically, the heating temperature in step S2 is 110 - 120°C.
[0064] The present invention also protects the use of the above polypropylene composite material in the preparation of household items, electronic components, household appliances, motor vehicle parts, and vehicle body parts. In particular, the above polypropylene composite material can be used to prepare parts with good thin-wall ablation resistance and toughness. In particular, it is applied in the preparation of electronic and electrical housing materials, especially suitable for battery covers of energy storage battery packs, power batteries of lithium batteries, protection boxes for electrical and electronic circuit boards, upper covers of new energy vehicle batteries, etc.
[0065] Compared with the prior art, the present invention has the following beneficial effects:
[0066] The present invention provides a halogen-free flame-retardant prepreg layer and a polypropylene composite material including the same. The halogen-free flame-retardant prepreg layer includes a glass fiber cloth and a prepreg. The thickness of the glass fiber cloth in the prepreg layer is 0.2 - 0.4 mm, and the grammage is 150 - 450 g / m 2 , the thickness of the halogen-free flame-retardant prepreg layer is 0.3 - 0.8 mm. The polypropylene composite material includes an ablation-resistant polypropylene composition layer and a halogen-free flame-retardant prepreg layer; the thickness of the polypropylene composite material ≤ 1.8 mm. The polypropylene composite material prepared by in-mold secondary injection molding has good ablation resistance and falling ball impact performance, and has good self-supporting performance. Detailed Embodiments
[0067] The following further elaborates the present invention in combination with specific embodiments. The embodiments are only used to explain the present invention and are not used to limit the scope of the present invention. The test methods used in the following embodiments are all conventional methods unless otherwise specified; the materials, reagents, etc. used are all reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0068] 1. Raw materials used in each embodiment and comparative example:
[0069] Polypropylene resin:
[0070] Polypropylene resin A: Copolymerized polypropylene, PP K7100, with a melt flow rate of 110 g / 10 min measured at 230°C and a load of 2.16 kg according to the ISO 1133-1:2022 standard, purchased from Sinopec Yanshan Petrochemical;
[0071] Polypropylene resin B: Copolymerized polypropylene, PP EP548R, with a melt flow rate of 28 g / 10 min measured at 230°C and a load of 2.16 kg according to the ISO 1133-1:2022 standard, purchased from CNOOC and Shell Petrochemical Company Limited;
[0072] Piperazine salts: Piperazine pyrophosphate, JNP-2, purchased from Sichuan Research & Design Institute of Fine Chemical Industry;
[0073] Melamine salts: Melamine polyphosphate, Melapur200-70, purchased from BASF SE;
[0074] Synergistic flame retardant: Silicon dioxide, XFI05, purchased from Xianfeng Nano Materials Technology Co., Ltd.;
[0075] Flux: Nano sepiolite, CALY 20, purchased from Tolsa Group, Spain;
[0076] Glass fiber cloth:
[0077] Glass fiber cloth 1: EWR200-100, thickness: 0.2 mm, grammage: 210 g / m 2 , purchased from Sichuan Glass Fiber Group Co., Ltd.;
[0078] Glass fiber cloth 2: EWR300-100, thickness: 0.3 mm, grammage: 290 g / m 2 , purchased from Sichuan Glass Fiber Group Co., Ltd.;
[0079] Glass fiber cloth 3: EWR400-100, thickness: 0.4 mm, grammage: 420 g / m 2 , purchased from Sichuan Glass Fiber Group Co., Ltd.;
[0080] Glass fiber cloth 4: EWR100-100, thickness: 0.1 mm, grammage: 120 g / m 2 , purchased from Sichuan Glass Fiber Group Co., Ltd.;
[0081] Glass fiber: Chopped glass fiber, ECS13-4.5-508A, purchased from Jushi Group Co., Ltd.;
[0082] Compatibilizer A: Maleic anhydride grafted polypropylene, UMEX 100TS, number average molecular weight is 9000, melting point is 136 °C, purchased from Sanyo Chemical Industries, Ltd.;
[0083] Compatibilizer B: Ethylene-octene copolymer grafted maleic anhydride, DuPont TM N493, purchased from DuPont;
[0084] Auxiliaries:
[0085] Antioxidant: A compound of hindered phenolic antioxidant (Irganox 1010) and phosphite antioxidant (Irganox 168) with a mass ratio of 1:2, both are commercially available;
[0086] Lubricant: EBS B50, commercially available;
[0087] It should be noted that the same raw materials used in the parallel experiments of each embodiment and comparative example in the present invention are from the same source.
[0088] 2. Parameter determination
[0089] (1) Thickness measurement of fiberglass cloth: According to ISO 5084, use a calibrated thickness gauge (25 mm probe, 1 kPa pressure). The specimens are conditioned at 23 ± 2 °C and 50 ± 5% RH for 24 hours, and 5 defect-free fiberglass cloth specimens with an area of 100 * 100 mm are cut. After calibration, place the specimen flat, slowly press the probe, measure 3 points for each specimen (avoiding nodes), and record the stable value. Calculate the overall mean.
[0090] (2) Grammage measurement of fiberglass cloth: According to ISO 3801, use a calibrated precision balance (accuracy 0.001 g) and a 100 cm 2 standard template. The specimens are conditioned at 23 ± 2 °C and 50 ± 5% RH for 24 hours, and 5 defect-free samples are cut avoiding the edges of the cloth roll. After precise cutting, remove the floating dust, weigh and calculate the grammage (g / m 2 = mass / area), example: 100 cm 2 specimen 1.2 g corresponds to 120 g / m 2 . Take the mean of the results.
[0091] (3) Thickness measurement of the halogen-free flame-retardant prepreg layer: According to ISO 5084, use a calibrated thickness gauge (25 mm probe, 1 kPa pressure). The specimens are conditioned at 23 ± 2 °C and 50 ± 5% RH for 24 hours, and 5 defect-free halogen-free flame-retardant prepreg cloth specimens with an area of 100 * 100 mm are cut. After calibration, place the specimen flat, slowly press the probe, measure 3 points for each specimen (avoiding nodes), and record the stable value. Calculate the overall mean.
[0092] (4) Thickness measurement of the polypropylene composite material: According to ISO 14129:1997, select a digital display thickness gauge (for hard materials). The specimens are conditioned at 23 ± 2 °C and 50 ± 5% RH for 24 hours, cut 5 defect-free specimens with an area of ≥ 50 × 50 mm, and calibrate the instrument after cleaning the surface. The pressure of the hard material probe is ≤ 10 kPa, for soft materials, increase the probe to 30 mm and reduce the pressure ≤ 5 kPa, measure 3 - 5 points for each specimen (avoiding the fiber enrichment area). Calculate the mean.
[0093] 3. Each halogen-free flame-retardant prepreg layer is prepared by the following method according to the formulations in Tables 1 - 2, including the following steps:
[0094] Mix the components other than the fiberglass cloth in the halogen-free flame retardant prepreg using a high-speed mixer to obtain a prepreg. Immerse the fiberglass cloth in the prepreg (at a temperature of 220 - 230 °C, apply the prepreg to the surface of the fiberglass cloth, and achieve double-sided impregnation through a sizing process. Use an infrared sensor to monitor the distribution of the adhesive solution in real-time and dynamically adjust the spraying amount and conveying speed to ensure the uniformity of the impregnation process), roll pressing, baking, film laminating, and coiling to obtain a halogen-free flame retardant prepreg layer; adjust the thickness of the halogen-free flame retardant prepreg layer by adjusting the impregnation amount of the prepreg on the surface of the fiberglass cloth.
[0095] Table 1 Prepreg Formulation (unit: parts by weight) Table 2 Halogen-Free Flame Retardant Prepreg Layer Formulation
[0096]
[0097] 4. The polypropylene composites described in each example and comparative example are prepared by the following method according to the formulations in Tables 3 - 5, including the following steps:
[0098] S1. Mix the components in the ablation-resistant polypropylene composition layer according to the formulation in Table 3 in a high-speed mixer for 1 - 3 minutes until uniform, and melt blend and extrude into pellets through a twin-screw extruder; the feeding speed of the twin-screw extruder is 250 - 350 rpm, the temperature of the first zone of the twin-screw extruder is 150 - 160 °C, the temperature of the second zone is 180 - 190 °C, the temperatures of the third to fifth zones are 210 - 230 °C, and the temperature of the die is 200 - 210 °C; the main machine speed of the twin-screw extruder is 300 - 500 rpm;
[0099] S2. Cut the halogen-free flame retardant prepreg layer in the preparation example to the product size: 500 mm * 500 mm, heat it at 110 - 120 °C for 10 - 20 min and then put it into an injection mold. Melt the injection pellets described in step S1 through an injection molding machine and inject them into the injection mold. After pressure holding and cooling, obtain a polypropylene composite; adjust the thickness of the polypropylene composite by adjusting the mold and the injection amount of the ablation-resistant polypropylene composition.
[0100] 5. Performance Testing:
[0101] (1) Ablation Resistance Performance Testing: Cut 100 mm * 100 mm square plates from the polypropylene composites prepared in each example and comparative example. According to the ablation material test method of GJB323A - 96, vertically impact the ablation-resistant polypropylene composition layer of the square plate with an oxygen-acetylene flame. The temperature of the oxygen-acetylene flame is as high as 1300 °C. Burn through or ablate the material until 600 s, and observe the deformation degree and burn-through time of the polypropylene composite during the combustion process;
[0102] (2) Falling ball impact performance test: The polypropylene composites prepared in each example and comparative example were tested according to the standard of GB9639.1-2008. The specimen size was a square plate of 100mm*100mm. A steel ball with a mass of 535g was dropped from different heights onto the center of the square plate. Each height needed to be tested three times. If no broken sample flew out in all three tests, the falling ball impact fracture height was recorded;
[0103] (3) Back surface temperature test: Cut a square plate of 100mm*100mm from the polypropylene composites prepared in each example and comparative example. According to the ablation material test method of GJB323A-96, the oxy-acetylene flame was vertically impinged on the square plate until the square plate could no longer support itself. Then, the temperature of the back surface of the square plate (the other side away from the flame) was tested using a FLUKE imaging test device;
[0104] (4) Flame retardant performance test: The polypropylene composites prepared in each example and comparative example were vertically burned according to UL94-2023.
[0105] Table 3 Formulation of the ablation-resistant polypropylene composition layer (unit: parts by weight)
[0106] Preparation Example A B C D Polypropylene Resin B 60.5 46.5 68.5 33.5 Piperazine Salt 17 20 15 35 Melamine Salt 9 10 10 5 Synergistic Flame Retardant 1 1 0.5 1.5 Flux / / 1 3 Glass Fiber 10 20 8 25 Compatibilizer B 2 2 1 5 Antioxidant 0.3 0.3 / 0.3 Lubricant 0.2 0.2 / 0.2
[0107] Table 4 Formulation and properties of the polypropylene composites of Examples 1-8
[0108] Example 1 2 3 4 5 6 7 8 Halogen-Free Flame Retardant Pre-Impregnated Layer 1 2 3 4 5 6 7 8 Ablation-Resistant Polypropylene Composition Layer A A A A A A A A Thickness (mm) 1.5 1.5 1.5 1.5 1.5 1.5 1.5 1.5 Flame Retardant Grade V-0 V-0 V-0 V-0 V-0 V-0 V-0 V-0 Falling Ball Impact Fracture Height (m) 3.5 2.7 2.3 2.5 2.5 3.4 2.8 2.3 Back Surface Temperature (°C) 158 165 175 166 165 158 166 175 Ablation Resistance Time (s) 600 600 600 600 600 600 600 600 Degree of Deformation (mm) 1.8 2.0 2.3 1.2 1.9 1.8 2.1 2.1
[0109] Table 5 Formulation and properties of the polypropylene composites of Examples 9-14 and Comparative Examples 1-3
[0110]
[0111]
[0112] The polypropylene composites prepared in each example of the present invention have good ablation resistance and falling ball impact performance, have good self-supporting effects (ablation resistance time and deformation degree). The ablation resistance time can all reach 600s, the deformation degree does not exceed 2.5mm, the back surface temperature during combustion does not exceed 180°C, and the falling ball impact height is not lower than 2m.
[0113] It can be seen from Comparative Examples 1-2 that when the thickness of the glass fiber cloth in the halogen-free flame retardant pre-impregnated layer is too low, the performance of the prepared polypropylene composite is poor, and the prepared polypropylene composite is easily burned through.
[0114] It can be seen from Comparative Example 3 that when the thickness of the halogen-free flame retardant pre-impregnated layer is too high, the ablation resistance performance of the prepared polypropylene composite decreases and it is easily burned through.
[0115] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, rather than limitations on the implementation manners of the present invention. For those of ordinary skill in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to enumerate all the implementation manners here. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A halogen-free flame retardant prepreg layer, characterized in that: It includes glass fiber cloth and prepreg, wherein the thickness of the glass fiber cloth in the prepreg layer is 0.2-0.4 mm, and the gram weight is 150-450 g / m 2 The thickness of the halogen-free flame retardant prepreg layer is 0.3 to 0.8 mm.
2. The halogen-free flame retardant prepreg layer according to claim 1, characterized in that: The prepreg comprises the following components calculated by weight:
3. The halogen-free flame retardant prepreg layer according to claim 1, characterized in that: The content of flame retardant in the prepreg is not less than 28 wt %, preferably 33-55 wt %.
4. The halogen-free flame retardant prepreg layer according to claim 2, characterized in that: Satisfy at least one of the following two conditions: (a) The number average molecular weight of the compatibilizer A is 5000-10000; the melting point is 130-140°C; preferably, the compatibilizer A is maleic anhydride grafted polypropylene. (b) The melt flow rate of the polypropylene resin A at 230° C. and a load of 2.16 kg is 60 to 150 g / 10 min.
5. A polypropylene composite material, characterized in that: It comprises an ablation-resistant polypropylene composition layer and the halogen-free flame-retardant prepreg layer according to any one of claims 1 to 4; the thickness of the polypropylene composite material is ≤1.8 mm.
6. The polypropylene composite material according to claim 5, characterized in that: The ablation-resistant polypropylene composition comprises the following components calculated in parts by weight:
7. The polypropylene composite material according to claim 6, characterized in that: Satisfy at least one of the following two conditions: (a) the compatibilizer B comprises maleic anhydride grafted polyolefin; preferably, the compatibilizer B is maleic anhydride grafted ethylene-octene copolymer; (b) The melt flow rate of the polypropylene resin B at 230° C. and a load of 2.16 kg is 20 to 50 g / 10 min.
8. A method for preparing the halogen-free prepreg layer according to any one of claims 1 to 4, characterized in that: The steps include: The components except the glass fiber cloth in the halogen-free flame retardant prepreg layer are mixed to obtain a prepreg, and the glass fiber cloth is impregnated with the prepreg, rolled, baked, coated, and rolled to obtain the halogen-free flame retardant prepreg layer.
9. A method for preparing the polypropylene composite material according to any one of claims 5 to 7, characterized in that: The steps include: S1. The components of the ablation-resistant polypropylene composition layer are uniformly mixed, melt blended, extruded and granulated to obtain injection molding pellets; S2. Cut the halogen-free flame-retardant prepreg layer to the target product size, put it into the injection mold after heating, inject the injection molding pellets described in step S1 into the injection mold, and obtain the polypropylene composite material after pressure maintenance and cooling.
10. Use of the polypropylene composite material according to any one of claims 5 to 7 in the preparation of energy storage battery packs, power battery lithium battery covers, electrical circuit board protection boxes, and new energy vehicle battery covers.
Citation Information
Patent Citations
Halogen-free flame-retardant polypropylene composite material and preparation method thereof
CN102850648A
Method for preparing halogen-free expanded flame-retardant glass fiber reinforced polypropylene board
CN108724853A
Glass fiber enhanced flame retardant polypropylene composite material for upper cover of battery pack and preparation method thereof
CN109181101A
Manufacturing method of thermoplastic prepreg sheet
JP2018070821A